ANALISIS PREFERENSI DAN PROSPEKTIF PARTISIPATIF DALAM PERENCANAAN PENATAAN DAN PENYESUAIAN ULANG LAHAN (LAND READJUSTMENT) KAWASAN KAMPUNG BRAGA BANDUNG - Ake Wihadanto; Baba Barus; Noer Azam Achsani; Deddy S. Bratakusumah (TATALOKA, 2017)
This research is purported to understand and map people’s preferences on rearrangement plan of the area. General description of people’s preferences is resulted by using qualitative descriptive analysis on data gained from interview and FGD. Furthermore, by employing Participatory Prospective Analysis (PPA) the people’s preferences has represented through the following key variables, those are transparency, people’s bargaining position, tenurial (ownership) system, communication, land value, institution/organization, location’s economic value, and level of conflict potential. Based on those variables, the future’s scenarios are constructed as follows: (1) Status quo; (2) Negative; (3) Positive; and (4) Progressive.  The way to anticipate the first two scenarios are to close or impede any room or possibilities of the scenarios’ emergence. Meanwhile, for the last two scenarios, the anticipation way is to promote or enhance the scenarios’ emergence, maintaining sustainability of the scenarios, as well as avoiding any ways that can reverse the scenarios’ direction. Both ways of anticipation should be carried out through transparency, communication, and institution.